Thoracoscopic Resection of a Rare Case of Hemangioma of the Azygos Venous Arch - Ma Husai; Cai Yixin; Zhang Ni; Wang Wenxin; Fu Xiangning (Case Reports in Surgery)
Hemangioma of the azygos venous arch is an exceedingly rare incident. This is a case of a thoracoscopic complete resection of a hemangioma of the azygos venous arch in a 37-year-old woman.